Ethanol Intoxication Impairs Respiratory Function and Bacterial Clearance and Is Associated With Neutrophil Accumulation in the Lung After Streptococcus pneumoniae Infection - Hulsebus, Holly J.; Najarro, Kevin M.; McMahan, Rachel H.; Boe, Devin M.; Orlicky, David J.; Kovacs, Elizabeth J. (Frontiers in Immunology, 2022)
Alcohol consumption is commonplace in the United States and its prevalence has increased in recent years. Excessive alcohol use is linked to an increased risk of infections including pneumococcal pneumonia, mostly commonly caused by Streptococcus pneumoniae. In addition, pneumonia patients with prior alcohol use often require more intensive treatment and longer hospital stays due to complications of infection. The initial respiratory tract immune response to S. pneumoniae includes the production of pro-inflammatory cytokines and chemokines by resident cells in the upper and lower airways which activate and recruit leukocytes to the site of infection. However, this inflammation must be tightly regulated to avoid accumulation of toxic by-products and subsequent tissue damage. A majority of previous work on alcohol and pneumonia involve animal models utilizing high concentrations of ethanol or chronic exposure, and offer conflicting results about how ethanol alters immunity to pathogens. Further, animal models often employ a high bacterial inoculum which may overwhelm the immune system and obscure results, limiting their applicability to the course of human infection. Here, we sought to determine how a more moderate ethanol exposure paradigm affects respiratory function and innate immunity in mice after intranasal infection with 104 colony forming units of S. pneumoniae. Ethanol-exposed mice displayed respiratory dysfunction and impaired bacterial clearance after infection compared to their vehicle-exposed counterparts. This altered response was associated with increased gene expression of neutrophil chemokines Cxcl1 and Cxcl2 in whole lung homogenates, elevated concentrations of circulating granulocyte-colony stimulating factor (G-CSF), and higher neutrophil numbers in the lung 24 hours after infection. Taken together, these findings suggest that even a more moderate ethanol consumption pattern can dramatically modulate the innate immune response to S. pneumoniae after only 3 days of ethanol exposure, and provide insight into possible mechanisms related to the compromised respiratory immunity seen in alcohol consumers with pneumonia.